The influence of lateral ejection on the thermal performance of matrix cooling channel. (5th July 2019) - Bu, Shi; Shi, Chengcheng; Zhang, Lin; Xu, Weigang; Liu, Lin
Highlights: Lateral ejection affects internal flow and heat transfer of matrix significantly. Holes next to the trailing side of sidewall turning gives better performance. Smaller holes and positive outflow orientation helps improve thermal performance. Heat transfer deteriorates with the straight flow exit blocked. Thermal performance can be improved with carefully designed lateral ejection. Abstract: Matrix is applied as an internal cooling scheme for gas turbine blades or vanes. This paper focuses on the Influence of lateral ejection on the cooling performance of matrix channel. The purpose is to improve the internal heat transfer and thermal performance of matrix channel with proper configurations of ejection holes. A validated computational method is used to obtain flow and heat transfer results of a typical matrix channel. The influence of location, dimension and outflow orientation of the ejection holes are discussed in detail. A channel with the absence of straight flow exit is also included for comparison. The result implies that the location of ejection is the most important factor that influences the cooling performance, holes in the downstream part of sidewall turning are better than those in the upstream part. More improvement can be achieved with smaller holes and positive outflow orientation. The blockage of the straight flow exit must be avoided because heat transfer deteriorates due to uneven distribution of coolant mass flow. The effect of reduction of internal coolant mass flow can be compensated by the increased turbulence with well-designed lateral ejection.